Storing Dried Cherrie (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides information from the literature on picking, transporting, sorting, inspecting, washing, immersing in an alkaline solution (blanching), balancing moisture, drying, and storing dry products. Including, during drying, stoves and furnaces must be built in such a way that they fully meet fire safety requirements. It was also mentioned that those working with caustic soda should be provided with special gowns, shoes, respirators, protective glasses and gloves.